Precision of region of interest‐based tri‐exponential intravoxel incoherent motion quantification and the role of the Intervoxel spatial distribution of flow velocities. Issue 6 (15th August 2022) - Simchick, Gregory; Hernando, Diego
Abstract : Purpose: The purpose of this work was to obtain precise tri‐exponential intravoxel incoherent motion (IVIM) quantification in the liver using 2D ( b ‐value and first‐order motion moment [ M 1 ]) IVIM‐DWI acquisitions and region of interest (ROI)‐based fitting techniques. Methods: Diffusion MRI of the liver was performed in 10 healthy volunteers using three IVIM‐DWI acquisitions: conventional monopolar, optimized monopolar, and optimized 2D ( b ‐ M 1 ). For each acquisition, bi‐exponential and tri‐exponential full, segmented, and over‐segmented ROI‐based fitting and a newly proposed blood velocity SDdistribution (BVD) fitting technique were performed to obtain IVIM estimates in the right and left liver lobes. Fitting quality was evaluated using corrected Akaike information criterion. Precision metrics (test–retest repeatability, inter‐reader reproducibility, and inter‐lobar agreement) were evaluated using Bland–Altman analysis, repeatability/reproducibility coefficients (RPCs), and paired sample t‐tests. Precision was compared across acquisitions and fitting methods. Results: High repeatability and reproducibility was observed in the estimations of the diffusion coefficient ( D tri  = [1.03 ± 0.11] × 10 −3  mm 2 /s; RPCs ≤ 1.34 × 10 −4  mm 2 /s), perfusion fractions ( F 1  = 3.19 ± 1.89% and F 2  = 16.4 ± 2.07%; RPCs ≤ 2.51%), and blood velocity SDs ( V b, 1  = 1.44 ± 0.14 mm/s and V b, 2  = 3.62 ± 0.13 mm/s; RPCs ≤ 0.41 mm/s) in the right liver lobe using the 2D ( b ‐ M 1 ) acquisition in conjunction with BVD fitting. Using these methods, significantly larger ( p  < 0.01) estimates of D tri and F 1 were observed in the left lobe in comparison to the right lobe, while estimates of V b, 1 and V b, 2 demonstrated high interlobar agreement (RPCs ≤ 0.45 mm/s). Conclusions: The 2D ( b ‐ M 1 ) IVIM‐DWI data acquisition in conjunction with BVD fitting enables highly precise tri‐exponential IVIM quantification in the right liver lobe.